Improving Kindergarten Children's Exploratory Ability through Project-Based Learning, Experimental Activities, and Loose Parts Media: A Classroom Action Research Study - Nor Anisa; Ahmad Suriansyah; Ratna Purwanti (Borneo Research and Education Center, 2025)
Exploratory ability is a central indicator of cognitive development in early childhood because it enables children to observe, question, manipulate objects, test ideas, and construct explanations from direct experience. The preliminary condition in a kindergarten class in Banjarmasin showed that only 4 of 12 children (33%) demonstrated developing exploratory ability, while 8 children (67%) remained in the not-yet-developed category. This classroom action research aimed to improve teacher activity, children's learning activity, and children's exploratory ability by integrating Project-Based Learning, experimental activities, and loose parts media. The participants were 12 kindergarten children aged 5-6 years (5 boys and 7 girls). The intervention was implemented in four meetings through planning, action, observation, and reflection. Data were collected through observation sheets, documentation, interviews, and an exploratory ability assessment rubric. The data were analyzed descriptively using percentages, cross-tabulation, and trend interpretation. The results showed consistent improvement across meetings. Teacher activity increased from a score of 25 (61%, fairly good) in Meeting 1 to 38 (93%, very good) in Meeting 4. Children's classical activity increased from 25% to 100%, and the proportion of children who achieved successful exploratory development increased from 16.7% to 100%. The findings indicate that the integration of project work, simple experiments, and open-ended loose parts materials can create a concrete, playful, and inquiry-oriented learning environment that supports children's exploratory behavior. The study contributes practical evidence for early childhood teachers who seek to transform monotonous worksheet-based instruction into active, child-centered, and developmentally appropriate learning.